PENGARUH GAYA HIDUP DAN KUALITAS LAYANANTERHADAP KEPUTUSAN PEMBELIAN DALAM JARINGAN - ROFIQ, AINUR (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract :According APJII growth of Internet users in Indonesia each year has increased, it is proven with an online purchases made ??by the Indonesian people by 27 % via the Internet. Lifestyle of today's society began to depend on the internet. This situation used to increase sales company primarily develops promotion through the internet. It is utilized by Gramedia to develop and expand the network marketing market. Gramedia provide more facilities at Gramedia online to give the consumer the convenience of making a purchase. The population is a consumer Gramedia online with aged 16-25 years old with a number of 110 respondents. Measuring instruments usedtechnically multiple linear regression analysis. The results showed thatnet oriented, innovative and price oriented not effected on online purchasing decision while service quality effected on online purchasing decision. Keywords:online lifestyle, service quality, and online purchasing decision